Pengaruh Likuiditas, Solvabilitas dan Ukuran Perusahaan terhadap Kinerja Keuangan pada Perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia Tahun 2016-2020 - Bambang Wahyudi Wicaksono; Edi Wahyu Wibowo; Albertus Karjono; Aditya Aditya (LITERATUS, 2022)
This study aims to determine the effect of Liquidity, Solvency and Firm Size on Financial Performance simultaneously and partially, in the Property, Real Estate and Building Construction sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Sampling using purposive sampling method. The research sample consisted of 44 companies with a 5-year period, namely 2014-2018. Financial report data was obtained from the Indonesia Stock Exchange, company web and IDN Financial. The research method used is associative research with secondary data. The analysis used in this research includes panel data test, classical assumption test, multiple linear regression analysis, coefficient of determination, f test, t test. The results showed that Liquidity, Solvency and Firm Size on Financial Performance. The results of the F test show that Liquidity, Solvency and Firm Size have a significant effect on Financial Performance, while the t test results show that Liquidity, Solvency and Firm Size have a significant effect on Financial Performance.